(untitled) (Precision Medicine Communications, 2022)
The effects of the gene SHOC2 in breast cancer patients and how it is regulated by the long noncoding RNA (lncRNA) MALAT1 were studied to elucidate the potential resistance mechanism to chemotherapy. Breast cancer cells were conferred resistance to Paclitaxel via titrating the cells with increasing doses of the drug. For predicting MALAT1 miRNA regulation, bioinformatic tools were used. It was observed that Paclitaxel resistance in the breast cancer cells was liked to an elevated expression of SHOC2 and MALAT1. They found that MALAT1 confers the Paclitaxel resistance by sequestering miR-497-5p to exaggerate the expression of SHOC1. Increased expression of SHOC2 and MALAT1 in breast cancer has demonstrated poorer therapeutic outcomes of Paclitaxel. They concluded that inhibition of MALAT1 and SHOC2 will lead to up-regulation of miR-497-5p, improving response to Paclitaxel in breast cancer patients. Pharmacogenomics. (2022) DOI: 10.2217/pgs-2022-0077.